Periprosthetic Fracture through a Unicortical Tracking Pin Site after Computer Navigated Total Knee Replacement - Matt Blue; Christian Douthit; Joel Dennison; Cyrus Caroom; Mark Jenkins (Case Reports in Orthopedics)
A rare complication from computer-navigated total knee arthroplasty is a fracture through the insertion site of a tracking pin. These pins are inserted across the femoral and tibial shafts either bicortically, transcortically, or unicortically and have a reported fracture incidence of 1.38%, with all published cases occurring after bicortical pin placement. In this case, a 60-year-old female suffered a femoral shaft fracture through a unicortically inserted computer navigation tracking pin 6 weeks after total knee arthroplasty. Her fracture was successfully fixated with an intramedullary nail with retention of the knee prosthesis. This case is important as it records the risk for a postoperative fracture through a unicortically inserted computer navigation pin.